Girls’ Delinquency in Contemporary Poland (Archives of Criminology, 2006)
The aim of the research was to learn about juvenile girls in Poland: who they are, what we know about their families, what kind of prohibited acts they commit. Another goal was to confront the results of the survey with the common beliefs. The society is convinced that girls became more cruel and violent and even petit crimes are committed more often. The research results do not confirm such a proposition.